On the distribution of the maximum of the difference of independent renewal processes with discrete time - Yezhov, I. I.; Kadankov, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We find the distribution of the maximum of the difference of two renewal processes with discrete time that is semicontinuous in discrete topology.